(untitled) (World Bulletin of Social Sciences, 2023)
In this article describes been established that reliance on such typologically heterogeneous linguistic material as phraseological units and paremias makes it possible to reconstruct folk ideas about the essence of the concept of "Food", to show differences in the understanding of this concept by representatives of the Uzbek and English cultures and to prove that lexical, phraseological and paremic units languages are in distributive relations, representing "their" sections of cultural concepts, giving them different depths, directly dependent on the significance of a concept or phenomenon in the life of an ethnic group.